EFFECT OF SOME ARTIFITIAL DIETS ON THE BIOLOGY OF DIATRAEA SACCHARALIS F. (LEPIDOPTERA: PYRALIDAE) AND ITS PARASITES - LASTRA-B., LUZ ADRIANA; GÓMEZ-L., LUIS ANTONIO (Revista Colombiana de Entomología, 1988)
During live generations, the suitability of tour diets 1: Beans-Villacorta; 2: Carrots-Gaviria; 3: Soy beans-Brewer and; 4: Cascin-Posso and Raigosa, was tested for rearing the sugarcane borer (SCB), Diatraea saccharalis (F). At the Centro Internacional de la Caña de Azúcar "Cenicaña- Apartado Aéreo 9138 Cali, Colombia. sometimes, their effect on the production of the parasites Paratheresia claripalpis and Metagonistylum minense reared on SCB larvae obtained from these diets, was measured in comparisom with field-collected larvae. Diets 2,3 and 4 produced normal alter 18 days. The shortest larval stage was 29,2, and 29,3 days and occurred in diet 2 and 3. The lowest parasitoid recovery was found in SCB larvae reared in diet 1 and field-collected larvae.